2004
DOI: 10.1177/0891988703261999
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Gambling among Elderly Veterans

Abstract: The purpose of the present study was to examine elderly patients, aged 60 and older, admitted to a residential gambling treatment program and to compare them to a younger cohort on a variety of mental health factors and measures. A retrospective chart review was performed for 37 elderly gamblers consecutively admitted to the Gambling Treatment Program of a VA center between December 1999 and December 2002. These elderly subjects were compared with a younger cohort of 98 gamblers. On intake, the gamblers comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…More evidence (especially in US populations) has accumulated to support the associations with affective disorders (Dannon et al, 2004;Kausch 2004 ;Petry et al, 2005;Westermeyer et al, 2005), anxiety disorders , personality disorders as a group (Ibanez et al, 2001;Petry et al, 2005), mania and impulse disorders (Grant and Kim, 2003;Kausch, 2003a).…”
Section: Summary Of Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…More evidence (especially in US populations) has accumulated to support the associations with affective disorders (Dannon et al, 2004;Kausch 2004 ;Petry et al, 2005;Westermeyer et al, 2005), anxiety disorders , personality disorders as a group (Ibanez et al, 2001;Petry et al, 2005), mania and impulse disorders (Grant and Kim, 2003;Kausch, 2003a).…”
Section: Summary Of Evidencementioning
confidence: 94%
“…He extended those findings (Kausch, 2003b) by studying suicide attempts in 114 veterans treated at the same in-patient unit, reporting that the substance use diagnosis increased the risk of suicide attempts in that cohort. Kausch (2004) also reported that among a group of 37 elderly US veterans treated for gambling as in-patients, depression was the most frequent co-occurring disorder. Pietrzak and Petry (2005) studied 237 pathological gamblers entering outpatient treatment in Connecticut, USA and found 16.5% fulfilled criteria for ASPD.…”
Section: Studies Of Gambling Behaviour and Other Co-occurring Behavioursmentioning
confidence: 95%
“…Older adult pathological gamblers were also found to have more problems with employment, but fewer problems in legal, social, and substance abuse domains than younger adult pathological gamblers (Petry, 2002). In a residential treatment program, older gamblers had fewer drug and alcohol problems than younger gamblers (Kausch, 2004). Older adult gamblers were also less likely to report a history of physical and emotional abuse, but sexual abuse and suicidal ideation were equally prevalent in older and younger gamblers.…”
Section: Introductionmentioning
confidence: 96%
“…The number of older problem gamblers is expected to increase concomitant with the increase in their demographic and in their gambling participation (Gerstein et al 1999a;Kausch 2004;McKay 2005;National Gambling Impact Study Commission 1999;Volberg 2002). They are targeted by casinos with promotions of free transportation, subsidized meals and discount coupons (McNeilly and Burke 2001;Stitt et al 2003;Tan and Wurtzburg 2004).…”
mentioning
confidence: 97%